Screening of olfactory function using odourized markers - Vodicka, J; Pellant, A; Chrobok, V (Rhinology, 2007)
BACKGROUND: The goal of our study was to create a psychophysical test for the screening of olfactory function on the basis of commercially available odourized markers (OM). There are six coloured markers in one package filled with different odourants at suprathreshold levels. In order to identify the best approach, we investigated five different variations of the technique. MATERIALS AND METHODS: Olfaction was investigated in 189 subjects. Healthy participants as well as patients suffering from olfactory disorders were tested. Initially subjects were tested by one of five methods using OM. Finally, the "Sniffin' Sticks" test (butanol odour threshold, odour identification) was performed. RESULTS: Correlation of the OM screening test and the "Sniffin' Sticks" ranged from 0.49 to 0.93 indicating that variations of the technique strongly influence the results of testing. The best technique for evaluating olfactory function included spontaneous naming of odours and odour identification from a list of four distractors. The sensitivity of this method was sufficient to determine anosmia. CONCLUSIONS: The odourized markers screening test can be used to screen for anosmia in the general population. However, the precise quantification of olfactory function is not possible, because of the relatively small amount of odours.
Keywords: Odorants; dospělí; Female; Adult; ženské pohlaví; Adolescent; Smell; diagnostické techniky a postupy; lidé; Diagnostic Techniques and Procedures; Aged, 80 and over; odoranty; Olfaction Disorders; poruchy čichu; Male; Aged; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; mladiství; čich; Humans